Study on the Effect of Rock Strength on the Macro-Meso Shear Behaviors of Artificial Rock Joints. (16th March 2022) - Jiang, Yujing; Zhang, Sunhao; Luan, Hengjie; Shan, Qinglin; Li, Baocheng; Wang, Dong; Jia, Chuanyang
Abstract : Understanding the shear properties of joints of rock masses is of great importance for engineering disaster prevention and control. In this paper, a systematic study of the macroscopic shear properties of joints of rock masses with different strengths is carried out using a combination of indoor tests and PFC 2D numerical simulations. The results show that (i) the shear stress curve of low-strength rock joints is strain-softening type, while high-strength rock joints are strain-hardening type, and high-strength rock joints are more sensitive to the change of roughness. (ii) With the increase of JRC, the damage mode of different strength rock joints gradually changes from "abrasion" to "abrasion + gnawing, " and the damage characteristics of the surface of high-strength rock joints are more significant. (iii) The contact force between particles is mainly concentrated on the joints. At the beginning of shear, the contact force is mainly distributed on the second-order roughness and gradually concentrated on the first-order roughness as the shear progresses. Compared with the low-strength rock joints, the contact force on the high-strength rock joints is larger and more widely distributed. (iv) Due to the change of contact force, the cracks keep expanding and the particle rotation arc keeps changing. The particles with larger rotational arcs are consistent with the location of crack distribution, and the cumulative number of cracks on the joints of high-strength rock is higher. (v) The total input energy and dissipation energy increase continuously with the shear, and the elastic energy tends to increase at the beginning of shear and then starts to decrease and gradually tends to be constant near the peak of shear stress. The total input energy and dissipation energy of the joints of the high-strength rock are larger, while the peak elastic energy of it is smaller.